Approaches to Education and Learning of the Quran and Al-Hadith - Aryanti Puspita Sari; Andi Abd. Muis; Ridwan; Siti Mahmudah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
In the face of the increasingly rapid development of the times, Islamic education is now faced with various challenges that require adjustment to the social, cultural, and technological dynamics that continue to develop. The influence of globalization and modernization has brought about major changes in people's way of thinking and expectations towards education, including Islamic education. Therefore, it is important to reconstruct Islamic educational thinking so that it remains relevant and effective in producing a generation that is able to compete in the modern era, without losing the fundamental values of Islamic teachings. This research aims to explore the challenges faced by Islamic education, as well as identify opportunities that can be used in the process of renewing their thinking. This study uses a qualitative approach with literature study as the main method to analyze existing problems and find solutions. It is hoped that the results of this research can contribute to developing the concept of Islamic education that is more flexible, inclusive, and able to respond to changes in the times quickly.